Collagenous Sprue - Hugh James Freeman (Canadian Journal of Gastroenterology)
Collagenous sprue is a small bowel mucosal lesion that has been historically associated with persistent diarrhea, progressive weight loss and severe malabsorption causing multiple nutrient deficiencies. A severe to variably severe mucosal lesion with distinct subepithelial collagen deposits occurs. Celiac disease has been intimately linked to collagenous sprue and, similar to celiac disease, small bowel ulceration, perforation and lymphoma may complicate the clinical course of collagenous sprue. In collagenous sprue, concomitant collagen deposits may also occur in gastric or colonic mucosal sites (or both), indicating that this unusual mucosal process may be very heterogeneous and far more extensive in the intestinal tract than previously appreciated. Moreover, reports of diagnosis during infancy suggest that the natural history of the disorder could be more prolonged than is currently appreciated. Finally, the collagen deposits, per se, may be due to different causes and, in some, even represent a novel paraneoplastic histopathological marker. Future studies are needed to more precisely define molecular and genetic biomarkers that identify homogeneous groups and permit the development of improved treatment strategies for this increasingly recognized disorder.